A new genus and two new species of the tribe Pexicopiini (Lepidoptera, Gelechiidae) from the Afrotropical region - Bidzilya, Oleksiy V.; Aarvik, Leif (Zootaxa, 2023)
A new genus, Falcipenna gen. nov., and two species, F. irinae sp. nov. (Kenya) and F. argenteomaculata sp. nov. (Kenya, Tanzania, South Africa), are described. Based on external and genital characters the new genus is placed in the subfamily Apatetrinae, tribe Pexicopiini. Within the tribe, the genus shows affinity to Harpagidia Raganot, 1895 and Sitotrogoides Sohn, Ponomarenko & Sakamaki, 2019. The differences between the new genus and allied genera are discussed. Adults of the new species are illustrated, including details of external morphology and male and female genitalia.